Marketing Strategy of Tengkiang Coffee Shop, Pulau Panggung Village, Semende Darat Laut District, Muara Enim Regency - wandri wandri; septianita Septianita; Henny Rosmawati (Universitas Galuh, 2026)
This study aims to analyze marketing strategies and factors that affect the success of marketing at Tengkiang Coffee Shop located in Pulau Panggung Village, Semende Darat Laut District, Muara Enim Regency. The research uses a qualitative descriptive approach with survey, interview, observation, and documentation methods. The data is analyzed using the marketing mix concept (7P) as well as a SWOT matrix to identify strengths, weaknesses, opportunities, and threats in marketing management. The results of the study show that the marketing strategy implemented is still conventional, relying on word-of-mouth promotion, without the use of digital media. The main strength of the business lies in the distinctive quality of local coffee, affordable prices, and a friendly and comfortable shop atmosphere. The suggested development strategy is horizontal integration by increasing product innovation, expanding distribution networks, and utilizing digital promotion. This research provides strategic recommendations for MSME actors in the rural culinary sector to strengthen competitiveness through local and digital-based marketing approaches. Keywords: Marketing Strategy, MSMEs, Coffee Shops, 7P Marketing Mix, SWOT